2009
DOI: 10.1038/emboj.2009.373
|View full text |Cite
|
Sign up to set email alerts
|

Modular architecture of Munc13/calmodulin complexes: dual regulation by Ca2+ and possible function in short-term synaptic plasticity

Abstract: Ca2+ signalling in neurons through calmodulin (CaM) has a prominent function in regulating synaptic vesicle trafficking, transport, and fusion. Importantly, Ca2+–CaM binds a conserved region in the priming proteins Munc13‐1 and ubMunc13‐2 and thus regulates synaptic neurotransmitter release in neurons in response to residual Ca2+ signals. We solved the structure of Ca2+4–CaM in complex with the CaM‐binding domain of Munc13‐1, which features a novel 1‐5‐8‐26 CaM‐binding motif with two separated mobile structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
76
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 68 publications
6
76
2
Order By: Relevance
“…This interaction domain is in agreement with the high-resolution nuclear magnetic resonance (NMR) structure derived from the CaM complex of the C-terminally elongated 34-amino-acid peptide Munc13-1 and is referred to as the C module (41). However, this published structure indicated that Trp-489 of Munc13-1 (position 26 of the motif) is embedded in the hydrophobic cleft of the N-terminal CaM domain to form a second interaction domain, the N module.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This interaction domain is in agreement with the high-resolution nuclear magnetic resonance (NMR) structure derived from the CaM complex of the C-terminally elongated 34-amino-acid peptide Munc13-1 and is referred to as the C module (41). However, this published structure indicated that Trp-489 of Munc13-1 (position 26 of the motif) is embedded in the hydrophobic cleft of the N-terminal CaM domain to form a second interaction domain, the N module.…”
Section: Discussionsupporting
confidence: 56%
“…Within this modular architecture, the complex adopts an extended conformation, as the C and N modules are connected by central flexible linkers in both CaM and Munc13-1 . Interestingly, NMR titration experiments indicated that the formation of the C module can occur at resting [Ca 2ϩ ], while a higher [Ca 2ϩ ] is required for the formation of the N module (41). This sequential binding mode likely enables CaM-Munc13 complexes to sense [Ca 2ϩ ] i over a broad concentration range, an essential feature to fulfill their role in Ca 2ϩ -dependent RRP size regulation.…”
Section: Discussionmentioning
confidence: 99%
“…CaM regulates vesicle priming, recruitment, and short-term plasticity by interactions with Munc13 (Junge et al, 2004;Zikich et al, 2008;Rodríguez-Castañeda et al, 2010;Lipstein et al, 2012), which is responsible for Ca 2+ /CaM-dependent replenishment at the calyx of Held (Lipstein et al, 2013). However, deletion of Munc13 in photoreceptors had no effect on vesicle tethering to the ribbon and only modest effects on synaptic transmission measured with ERG recordings (Cooper et al, 2012), pointing toward a limited involvement of Munc13 in vesicle replenishment in photoreceptors.…”
Section: Potential Molecular Mechanisms Of Ca 2+ /Cam Effectsmentioning
confidence: 87%
“…Among the ϳ40 structures of CaM⅐protein/peptide complexes deposited in the Protein Data Bank, only one structure possesses features highly similar to those observed in the CaM⅐MA-(8 -43) structure. The bipartite binding motif has been identified for CaM bound to Munc13-1, a regulator of synaptic vesicle priming (81). Munc13-1 binds the C-terminal lobe of CaM via its long N-terminal helix that is connected by a long flexible linker to a very short ␣-helix, which binds the N-terminal lobe of CaM (81).…”
Section: Discussionmentioning
confidence: 99%
“…The bipartite binding motif has been identified for CaM bound to Munc13-1, a regulator of synaptic vesicle priming (81). Munc13-1 binds the C-terminal lobe of CaM via its long N-terminal helix that is connected by a long flexible linker to a very short ␣-helix, which binds the N-terminal lobe of CaM (81). In another structure of the CaM complex with a peptide derived from vacuolar calcium-ATPase BCA1 protein, two CaM-interacting ␣-helices in the BCA1 peptide are connected by a very short and rather rigid linker (82); the central part of the CaM⅐BCA1 complex lacks the flexibility observed in the structures of CaM bound to Munc13-1 or MA- (8 -43).…”
Section: Discussionmentioning
confidence: 99%